A theoretical study on propagation of guided waves in a fluid layer overlying a solid half-space - Nguyen, Phuong-Thuy; Phan, Haidang (Vietnam Journal of Mechanics, 2019)
Ultrasonic guided waves propagating in a non-viscous fluid layer of uniform thickness bonded to an elastic solid half-space is theoretically investigated in this article. Based on the boundary conditions set for the joined configuration, a characteristic dispersion equation is found and new expressions for free guided waves are introduced. Closed-form solutions of guided waves generated by a time-harmonic load are derived by the use of elastodynamics reciprocity theorems. Through calculation examples, it is shown that the obtained computation of the lowest wave mode approaches the result of the Rayleigh wave in the solid half-space as the layer thickness approaches zero. The aim of the present work is to improve the understanding of wave motions in layered half-spaces for potential applications in the area of bone quantitative ultrasound.